Comparisons between in situ backscattering measurements and inversion products using an optical time series - Gernez, P.; Antoine, David; Vellucci, V. (ASLO Aquatice Sciences, 2009)
The particulate backscattering coefficient (bbp) is a key factor in estimating Particulate Organic Carbon (POC) and Particle Size Distribution (PSD) from ocean color satellite measurements. A time series of Inherent and Apparent Optical Properties (IOPs and AOPs) is collected at a deep ocean mooring (BOUSSOLE project) in the north western Mediterranean Sea (60 km offshore Nice, France). All data are simultaneously recorded every 15 minutes at 4 and 9 m depth. This data base allows comparison of bbp measurement with inversion product, either derived from concomitant underwater AOPs measurement or from remotely sensed satellite ocean color. The aims of this presentation are: (1) to describe the variability in bbp at time-scales of days and seasons; (2) to examine the uncertainties of the inversion products.